Ontologies giving semantics to network management models. - Lopez de Vergara, J.E (IEEE Network : the magazine of global information exchange)
The multiplicity of network management models may imply in some scenarios the use of multiple management information languages defining the resources to be managed. Each language has a different level of semantic expressiveness, which is not easily measurable. Also, these management information models cannot be easily integrated due to the difficulty of translation of the semantics they contain. The article proposes the use of ontologies as a new approach to improving the semantic expressiveness of management information languages. Ontologies are currently used, for instance, to provide Web pages and Web services the semantics they usually lack (known today as the semantic Web). Applying ontologies to management information languages can also be useful for integration of information definitions specified by different management languages and adding behavior information to them.